2021
DOI: 10.55230/mabjournal.v50i1.9
|View full text |Cite
|
Sign up to set email alerts
|

Microbial-Induced Calcite Precipitation: A Milestone Towards Soil Improvement

Abstract: Microbial-induced calcite precipitation (MICP) is a natural process that offered various applications in the engineering field materials and construction industry. It has recently emerged as an innovative, eco-friendly, and economically engineeredprocess. One of the successful MICP methods of improving the engineering properties of soils is ureolysis. The ureolysis drove the process of precipitate calcite which binds soil particles within the soil matrix thus enhance soil characteristicssuch as stiffness, perm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 109 publications
(204 reference statements)
0
8
0
Order By: Relevance
“…To overcome this problem, Chunxiang et al (2009) suggested that both cementation solution and bacterial solution be introduced simultaneously since the bacterial cell wall is composed of numerous negative charges (Dardau et al, 2021) and thus, if positively charged ions are introduced first without urea, Ca 2+ ions spontaneously adhere to the bacterial surface (even in the presence of urea), severely influencing and delaying bacterial activity. Thus, enzyme degradation is hindered no matter when urea is added, as bacterial surfaces would be coated with Ca 2+ , which impairs urea passage.…”
Section: Cacl 2 Impact On Soil Permeabilitymentioning
confidence: 99%
“…To overcome this problem, Chunxiang et al (2009) suggested that both cementation solution and bacterial solution be introduced simultaneously since the bacterial cell wall is composed of numerous negative charges (Dardau et al, 2021) and thus, if positively charged ions are introduced first without urea, Ca 2+ ions spontaneously adhere to the bacterial surface (even in the presence of urea), severely influencing and delaying bacterial activity. Thus, enzyme degradation is hindered no matter when urea is added, as bacterial surfaces would be coated with Ca 2+ , which impairs urea passage.…”
Section: Cacl 2 Impact On Soil Permeabilitymentioning
confidence: 99%
“…Corals produce from a single polyp into 3D complex communities held together by a mineralized scaffold, and bacteria construct architectonically complex 3D communities that frequently contain mineral and organic extracellular component (Keren-Paz and Kolodkin-Gal, 2020). Unlike human bones and teeth, designed with calcium phosphate mineral (assembled over hydroxyapatite or apatite) over a collagen template (Jeong et al, 2019), scaffolds formed by soil and marine bacteria and corals are frequently composed of calcium carbonate (Dhami et al, 2013;Phillips et al, 2013;Dardau et al, 2021), although accumulation of crystalline calcium phosphate was also reported (Hirschler et al, 1990). Crystals formed over the organic templates are either vaterite [generated by cyanobacteria (Zafar et al, 2022)], aragonite [generated by corals, and microalgae/cyanobacteria (Xu et al, 2019)] and calcite formed by Bacillus subtilis and the Bacillus phylum members (Oppenheimer-Shaanan et al, 2016;Keren-Paz et al, 2022), Pseudomonas aeruginosa (Li et al, 2015;Cohen-Cymberknoh et al, 2022), and cyanobacteria (Kranz et al, 2010).…”
Section: Current Challenges In Constructionmentioning
confidence: 99%
“…, where the source of CO 2 can be a byproduct of bacterial metabolism or the atmosphere (Dhami et al, 2013). The growth of calcium carbonate crystals occurs in layers while the biogenic (organic) environment and organic polymeric substances influence crystal shape and morphology (Weiner and Addadi, 2011;Zhang et al, 2016).…”
Section: Molecular Mechanisms Promoting the Production Of Cementitiou...mentioning
confidence: 99%
See 1 more Smart Citation
“…Biocalcification also referred to as microbially induced calcite precipitation (MICP) is a biomineralization technique involving a biochemical process of precipitating calcium carbonate (CaCO 3 ) crystals induced by active ureolytic bacterial activity due to urea hydrolysis (ureolysis) occurring within the environment (Zamer et al 2018;Chen et al 2019;Yang et al 2020). The success of the MICP process is promoted primarily by ureolytic bacterial species such as Bacillus sphaericus, Pararhodobacter sp., Mor-ganella morgana, Bacillus licheniformis and Bacillus cereus which are capable of utilizing urea as a source of nitrogen by passively diffusing or actively transporting the urea into the cytoplasm of the cell and the bacterial cell wall acting as nucleation sites (Dardau et al 2021). In search for alternative soil improvement technology with minimal environmental consequences, less adverse effect on the ecosystem and maintaining ecological balance (Khaliq & Ehsan 2016), over conventional methods (cement, chemical grouting & deep mixing technique) that varied in terms of environmental impact, cost, penetration depth, energy consumption and treatment uniformity which portrays their merits and demerits (Hiranya et al 2018;Duo et al 2018;Bui Truong et al 2020), and advances in material and geotechnical research, led to the development of an innovative, novel bio-mediated soil improvement technique utilizing ureaseproducing bacteria as potential agents.…”
Section: Introductionmentioning
confidence: 99%